The effect of filling techniques on compressive strength of dental composites - Pizi, Eliane C. G.; Martins, Luís R. M.; Soares, Carlos José; Correr, Américo B.; C. Sobrinho, Lourenço; Consani, Simonides (Brazilian Dental Science, 2010)
The aim of this study was to evaluated the effect of filling techniques on compressive strength of six dental composites. The composites (Z100, Surefil, P60, Definite, Prodigy Condensable, and Solitaire) were placed in circular aluminum molds with 2.5 mm in inner diameter and 5 mm in height. Each composite was divided into two groups (n=8): Group 1 – the composite was placed in the mold in bulk increment of 5 mm thick, covered with Mylar strip and photoactivated for 40 seconds; and, Group 2 – the composite was placed in two increments of 2.5 mm thick each and photoactivated for 40 seconds for each increment. Afterwards, the specimens were stored in a dark container, with distilled water at 37o C for 24 hours before test. After storage, the specimens were submitted to compressive strength in a Instron device at a crosshead speed of 1.0 mm/minute. Data were submitted to ANOVA and Test t – Student (5%) and showed that for each increment of condensable composite should not be greater than 2 – 3 mm and must be properly polymerized to get optimal mechanical properties. Z100 and P60 composites showed higher compressive strength values, while the lowest values were found for Prodigy and Solitaire.